Analytical approach for describing the collapse of surface asperities under compressive stress during rapid solid state bonding. (February 2017) - Chen, Gaoqiang; Feng, Zhili; Chen, Jian; Liu, Lei; Li, Han; Liu, Qu; Zhang, Shuai; Cao, Xiong; Zhang, Gong; Shi, Qingyu
Abstract: Many material manufacturing technologies, such as friction stir welding, rely on rapid solid state bonding to join metal surfaces. In this letter, a differential equation is developed to formulate the growing of the interfacial bonded area owing to the collapse of surface asperities under compressive stress during rapid solid state bonding of metal surfaces. The effect of pressure, temperature and bonding time on the growing of bonded area is discussed. The proposed approach is verified by experimental data. Graphical abstract: